Distractor-induced saccade trajectory curvature reveals visual contralateral bias with respect to the dominant eye - Romain Chaumillon; Nadia Alahyane; Patrice Senot; Christelle Lemoine-Lardennois; Karine Doré-Mazars; Dorine Vergilino-Perez; Alain Guillaume (Scientific Reports, 2022)
Abstract The functional consequences of the visual system lateralization referred to as “eye dominance” remain poorly understood. We previously reported shorter hand reaction times for targets appearing in the contralateral visual hemifield with respect to the dominant eye (DE). Here, we further explore this contralateral bias by studying the influence of laterally placed visual distractors on vertical saccade trajectories, a sensitive method to assess visual processing. In binocular conditions, saccade trajectory curvature was larger toward a distractor placed in the contralateral hemifield with respect to the DE (e.g., in the left visual hemifield for a participant with a right dominant eye) than toward one presented in the ipsilateral hemifield (in the right visual hemifield in our example). When two distractors were present at the same time, the vertical saccade showed curvature toward the contralateral side. In monocular conditions, when one distractor was presented, a similar larger influence of the contralateral distractor was observed only when the viewing eye was the DE. When the non dominant eye (NDE) was viewing, curvature was symmetric for both distractor sides. Interestingly, this curvature was as large as the one obtained for the contralateral distractor when the DE was viewing, suggesting that eye dominance consequences rely on inhibition mechanisms present when the DE is viewing. Overall, these results demonstrate that DE influences visual integration occurring around saccade production and support a DE-based contralateral visual bias.